2014
DOI: 10.2215/cjn.02140214
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sarcopenia with eGFR and Misclassification of Obesity in Adults with CKD in the United States

Abstract: Background and objectives Muscle wasting is common among patients with ESRD, but little is known about differences in muscle mass in persons with CKD before the initiation of dialysis. If sarcopenia was common, it might affect the use of body mass index for diagnosing obesity in people with CKD. Because obesity may be protective in patients with CKD and ESRD, an accurate understanding of how sarcopenia affects its measurement is crucial.Design, setting, participants, & measurements Differences in body composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
91
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 40 publications
3
91
0
1
Order By: Relevance
“…The potentially nephrotoxic drugs, particularly aminoglycosides, require a regular serum monitoring with frequent assessment of renal function [estimated glomerular filtration rate (eGFR) and creatinine] and this is of great importance especially in frail sarcopenic patients. 38 Since the elderly often have a compromised cardiac function, fluids and electrolytes intravenously should be administered with caution, considering the water balance, the change in body weight and the state of repletion measurable by ultrasound evaluation of the caval diameter. 39 Another event to assess in the elderly is secondary diarrhea in antibiotic-associated colitis, which is common if you are using ampicillin, cephalosporins or clindamycin.…”
Section: Therapy In the Elderly Population: General Considerationsmentioning
confidence: 99%
“…The potentially nephrotoxic drugs, particularly aminoglycosides, require a regular serum monitoring with frequent assessment of renal function [estimated glomerular filtration rate (eGFR) and creatinine] and this is of great importance especially in frail sarcopenic patients. 38 Since the elderly often have a compromised cardiac function, fluids and electrolytes intravenously should be administered with caution, considering the water balance, the change in body weight and the state of repletion measurable by ultrasound evaluation of the caval diameter. 39 Another event to assess in the elderly is secondary diarrhea in antibiotic-associated colitis, which is common if you are using ampicillin, cephalosporins or clindamycin.…”
Section: Therapy In the Elderly Population: General Considerationsmentioning
confidence: 99%
“…These figures are intriguingly similar to our report on Swedish patients on dialysis (10): excess fatness was present in up to 65% of our patients, and the majority (.50%) of them was misclassified by BMI cutoffs. The reason for this considerable misclassification in both studies was, by subtraction, reduced muscle mass (sarcopenia), which in the study by Sharma et al (8), increased almost linearly across worsening CKD strata and conveyed the extreme situation that 98% of obese individuals with sarcopenia were not correctly diagnosed by BMI.…”
mentioning
confidence: 91%
“…Therefore, differences in the prevalence of sarcopenia in this study might just reflect differences in the age distribution of patients with and without CKD. It is noteworthy that, in the work by Sharma et al (8), the linear increase in patients with sarcopenia across worsening CKD strata flattened out after standardization by age, and although Foley et al (16) reported a higher prevalence of sarcopenia in individuals with CKD stage $3 in the NHANES than in those with normal renal function, simple adjustment for age abrogated this difference. Both aging and the abovementioned body compositional changes lead to frailty.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Sarcopenic obesity was first defined by Baumgartner, who represents a reduced skeletal muscle mass coupled with an increase in fat mass 5, 6, 7. Sarcopenic obesity specifically was highly prevalent among persons with CKD and not those without CKD 8. Sarcopenic obesity may have a particularly poor prognosis and associated with an increased risk of death in patients with end‐stage renal disease (ESRD) 9.…”
mentioning
confidence: 99%